Arsenic adsorption from water iron impregnated granular activated carbon : a batch study - Wong, Ai Xin Lei Lei. (2011)
Chronic arsenic (As) poisoning has been a long standing problem in many countries due to the polluted drinking water sources millions of people are dependent upon. This problem is especially pronounced in Bangladesh where as many as 40 million people are believed to be at risk of As poisoning. This report explores the feasibility of iron impregnated granular activated carbon (GAC-Fe) as an adsorbent for dissolved As in water through batch studies. It is found that GAC-Fe has a high affinity for As and is able to adsorb 99.2% of As(V) when the initial concentration is 500 μg/l (the average concentration of many polluted sources in Bangladesh). The final solution measured 4 μg/l, which is well below the state limits in Bangladesh of 50 μg/l and also meet the new WHO maximum contaminant level (MCL) of 10 μg/l.